2013
DOI: 10.1590/s1415-790x2013000200026
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de fatores que interferem na amamentação na primeira hora de vida

Abstract: Help provided by the health team to breastfeeding at birth, Step 4 of the Baby-Friendly Hospital Initiative, as well as non black women, multiparous women, receiving pre-natal care, vaginal delivery and appropriate birthweight contributed to breastfeeding in the first hour of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
2
27

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 15 publications
2
17
2
27
Order By: Relevance
“…In terms of maternal sociodemographic characteristics, the groups did not show significant variations, probably due to the relationship between economic class and delivery type (36) . In a study carried out in a maternity hospital in Rio de Janeiro, multiparous women were more likely to breastfeed in the first hour (32) , as in this study. It may be that multiparous women gave birth to their offspring in a short time and underwent actions favorable to early breastfeeding at first birth, which reflected positively on the second birth.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In terms of maternal sociodemographic characteristics, the groups did not show significant variations, probably due to the relationship between economic class and delivery type (36) . In a study carried out in a maternity hospital in Rio de Janeiro, multiparous women were more likely to breastfeed in the first hour (32) , as in this study. It may be that multiparous women gave birth to their offspring in a short time and underwent actions favorable to early breastfeeding at first birth, which reflected positively on the second birth.…”
Section: Discussionsupporting
confidence: 54%
“…This association may be an indication that mothers who had already been advised about the importance of breastfeeding their child soon after birth became more available to this act, or asked for more help from health professionals who attended them in order to implement it. A study carried out in a maternity hospital in the city of Rio de Janeiro revealed that less than half of the puerperae knew about the possibility of breastfeeding in the delivery room (32) .…”
Section: Discussionmentioning
confidence: 99%
“…Data from Uganda PNDS, conducted in 2006, showed that women who sought prenatal care were more likely to breastfeed within the first hour (6 to 7%) when compared to those who did not seek prenatal care 37 . Cross-sectional study conducted in Rio de Janeiro indicated that get prenatal care was a protective factor for non-breastfeeding within one hour of birth (PR = 0.23) 19.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have investigated the factors associated with breastfeeding within one hour of birth in the Brazilian population 15,[18][19][20][21][22] and none of them were conducted in the Midwest region. This study aimed at investigating the prevalence of breastfeeding in the first hour of life, as well as the factors that interfered in this practice in the Federal District, the country capital, in 2011.…”
Section: Palavrasmentioning
confidence: 99%
“…Pesquisas demonstraram que prevalência do aleitamento materno na primeira hora de vida foi reduzida pela metade entre as mães submetidas ao parto cesariano, podendo estar relacionado à anestesia e aos procedimentos cirúrgicos ocorridos no pós-parto (OLIVEIRA et al, 2010;VIEIRA et al, 2010;PEREIRA et al, 2013;MEZZACAPPA;FERREIRA, 2016). Há maior facilitação para o estabelecimento da lactação mais precoce e efetiva no parto vaginal, uma vez que não há o fator dor incisional ou o efeito pós-anestésico da cesárea, podendo dificultar as primeiras mamadas e também pelo fato da participação mais ativa da mulher durante o parto (BOCCOLINI et al, 2011;DAVANZO et al, 2013;PEREIRA et al, 2013;MEZZACAPPA;FERREIRA, 2016).…”
Section: Aleitamento Maternounclassified